PERJUANGAN KELOMPOK TANI INTERNASIONAL DALAM MELAWAN PROGRAM LIBERALISASI PERTANIAN GLOBAL (Studi tentang perlawanan La Via Campesina terhadap program liberalisme pertanian WTO) - Adi Joko Purwanto (SPEKTRUM, 2012)
Abstract The agricultural sector is the most sensitive sectors both domestic and International politics.  Since trade liberalization began and banner proclaimed, the central sector of life for most people in developing countries, is also covered and for liberalization. This paper describes an international social movement resistance (La Via Campesina/ international peasant movement) in the struggle against global agricultural liberalization program run by World Trade Organization (WTO). In conducting the study, researchers used qualitative methods. This method is particularly relevant because it can answer the problem and qualitative research are better able to get in on a deeper exploration. The facts and the cases raised in the field of qualitative research is not as dead but moving data and dialectical in a more complex history.   Keywords : Neo-Liberalism, Agricultural liberalization, Social Movement, International peasant movement, La Via Campesina, World Trade Organization (WTO).